Sistem Pendukung Keputusan Penentuan Prioritas Pemesanan Produk Bengkel Las menggunakan Metode Weighted Product Berbasis Web - Andri Nata; Edi Kurniawan; Nasrun Marpaung (Neolectura, 2022)
The purpose of this study is to make a computerized system to build a decision support system at the SAHABAT welding shop, where later this decision support system can help determine product ordering priorities. to fulfill requests based on orders from customers. The method of data collection is in the form of direct observation to the object of research, namely the SAHABAT Welding Workshop. System development methods include data analysis, system design, system development, system testing and decision making. This system helps users in determining the priority of ordering products so that orders can be carried out in a timely and profitable manner. The data used is primary data. The research uses PIECES analysis which uses the CI framework and MySQL as the database. System development methods include data analysis, system design, system development, system testing and decision making. This system helps users in determining the priority of ordering products so that orders can be carried out in a timely and profitable manner. The results of this study are product orders to be designed, starting with input data, which is a stage that begins with inputting order data in the form of criteria and alternatives. The inputted criteria and alternative data is processed and then stored into the database (basic data or database). Then the output data is obtained, namely the analysis report.